THE EFFECT OF SCHOOL CLIMATE ON THE PERFORMANCE OF EDUCATORS AT PUBLIC SENIOR HIGH SCHOOLS OF PINRANG REGENCY - Walid, Abdul; Juhannis, Hamdan; Mania, St. (Jurnal Diskursus Islam, 2022)
This paper explicitly describes school climate’s effect on educators’ performance at Public Senior High Schools of Pinrang Regency. The research method of this study was quantitative, with the research ex-post facto. The total population was 422 education workers. The Yamane formula determined the sample of this study; the number of samples was 80 educators at Public Senior High Schools of Pinrang Regency. The research instrument used was a questionnaire. The data obtained were processed using the SPSS for windows version 20.00 application. This study’s data analysis used descriptive and inferential statistical analysis. The study results concluded that: 1) the description of the school climate with the statement results of 83.01%; 2) the description of the performance of educators is 84.35% with the interpretation of the three variables showing that they are in the gratifying category. 3) the school climate has an effective contribution of 58.37% and a relative contribution of 51.19% to the performance of educators. The implication of this study refers to the need for systemic and systematic steps in improving the school climate and the performance of educators from the government at the Public Senior High School of Pinrang Regency.